Pro- and Anti-inflammatory Biomarkers Responses after Aerobic Training in Heart Transplant Recipients: A Systematic Review and Meta-analysis - Franzoni, Leandro T.; da Motta, Stephanie Bastos; Carvalho, Gabriel; Costa, Rochelle Rocha; Ahner, Mabel Marciela; Saffi, Marco Aurélio Lumertz; Pereira, Alexandre Araújo; Pereira, Adamastor Humberto; da Silveira, Anderson Donelli; Stein, Ricardo (Current Cardiology Reviews, 2024)
Background: Physical exercise (PE) may improve plasma concentration of interleukin- 6 (IL-6), tumor necrosis factor-alpha (TNF-alpha), and adiponectin (adpN) in heart transplant (HT) patients. However, no consistent data is available on this population. Aim: Thus, we aimed to conduct a systematic review and meta-analysis on the effects of PE over these pro- and anti-inflammatory biomarkers in HT patients. Methods: Following the guidelines established by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 statement, we conducted a systematic literature search in the PubMed, Cochrane, and Scopus databases. Outcomes included IL-6, TNF-alpha, and adpN. Effect size (ES) was calculated using the standardized mean difference with a 95% confidence interval (CI). Results: The PE group (aerobic modality) was associated with reduced IL-6 compared to the control group (ES: −0.53; 95% CI: −0.99 to −0.06 pg/mL; P = 0.026). However, the PE group did not show a significant effect on TNF-alpha and adpN levels (ES: −0.33; 95% CI: −0.79 to 0.13; P = 0.16 and ES: −0.20; 95% CI: −0.70 to 0.30 pg/mL; P = 0.444, respectively). Conclusion: PE is associated with IL-6 reductions, although TNF alpha and adpN did not change after this intervention in HT patients. Therefore, PE is an effective intervention to downregulate IL-6 in post-HT patients.
Keywords: aerobic modality